Word consciousness and individual application of academic vocabulary through written, oral, and visual response to historical fiction and nonfiction literature in fifth-grade social studies. - Jack, Ashlie R. (Kansas State University, 2011)
The purpose of this qualitative case study was to explore and identify the word consciousness and individual application of academic vocabulary through the use of vocabulary reader response journals, authentic discussions, and multigenre response projects from a thematic social studies unit using historical fiction and nonfiction literature that was integrated in the fifth-grade curriculum. This qualitative research study took place in a third-fifth grade school in a Midwest setting with 23 fifth-grade students over the course of 14 weeks. Data were analyzed from eight of the 23 students. Multiple data sources for each literature selection were analyzed to reveal how fifth-grade students’ written, oral, and visual response to historical fiction and nonfiction literature demonstrate word consciousness and individual application of academic vocabulary. Conclusions indicate that student participants prefer the opportunity to create a visual image or write a statement to confirm the meaning of an academic vocabulary word in their vocabulary reader response journals. While orally discussing the academic words, the participants chose the evaluation approach. This authentic discussion response option allowed the students the opportunity to share their personal understanding, opinion, or inference for each word. Written and visual response was also afforded through the multigenre response projects. These projects revealed the individual application through conventional and nonconventional usage of the academic terms from each literature selection.
Keywords: Literacy; Vocabulary; Reading; Authentic discussions; Reader response; Multigenre projects; Reading Instruction (0535); Teacher Education (0530)